Cardiac pacing for severe childhood neurally mediated syncope with reflex anoxic seizures. Issue 6 (1st December 1999) - McLeod, K A; Wilson, N; Hewitt, J; Norrie, J; Stephenson, J B P
Abstract : OBJECTIVE: To determine whether permanent cardiac pacing could prevent syncope and seizures in children with frequent severe neurally mediated syncope, and if so whether dual chamber pacing was superior to single chamber ventricular pacing. METHODS: Dual chamber pacemakers were implanted into 12 children (eight male, four female) aged 2–14 years (median 2.8 years) with frequent episodes of reflex anoxic seizures and a recorded prolonged asystole during an attack. The pacemaker was programmed to sensing only (ODO), single chamber ventricular pacing with hysteresis (VVI), and dual chamber pacing with rate drop response (DDD) for four month periods, with each patient allocated to one of the six possible sequences of these modes, according to chronological order of pacemaker implantation. The parent and patient were blinded to the pacemaker mode and asked to record all episodes of syncope or presyncope ("near miss" events). The doctor analysing the results was blinded to the patient and pacemaker mode. RESULTS: One patient was withdrawn from the study after the pacemaker was removed because of infection. In the remaining children, both dual chamber and single chamber pacing significantly reduced the number of syncopal episodes compared with sensing only (p = 0.0078 for both). VVI was as effective as DDD for preventing syncope, but DDD was superior to VVI in reducing near miss events (p = 0.016). CONCLUSIONS: Permanent pacing is an effective treatment for children with severe neurally mediated syncope and reflex anoxic seizures. VVI is as effective as DDD in preventing syncope and seizures, but DDD is superior in preventing overall symptoms.